Synthesis and evaluation of NaNi0.5Co0.2Mn0.3O2 as a cathode material for Na-ion battery. Issue 10 (1st August 2016) - Xu, Han; Zong, Jun; Chen, Sen; Ding, Fei; Lu, Zhi-Wei; Liu, Xing-Jiang
Abstract: NaNi0.5 Co0.2 Mn0.3 O2 is synthesized by acetate decomposition method and investigated as a cathode material for sodium ion batteries. Galvanostatic charge and discharge of NaNi0.5 Co0.2 Mn0.3 O2 between 2.0 and 4.25 V provides the reversible capacity of 164.8 mA h g −1 at 0.05 C. This material also demonstrates great rate-capability and can de-intercalate 80 mA h g −1 even at 10 C. In addition, the NaNi0.5 Co0.2 Mn0.3 O2 exhibits a great cyclic performance (retaining 97.5% after 50 cycles) at the charge/discharge rate of 0.5 C.